2021
DOI: 10.1186/s12911-021-01639-y
|View full text |Cite|
|
Sign up to set email alerts
|

Predictive modeling for 14-day unplanned hospital readmission risk by using machine learning algorithms

Abstract: Background Early unplanned hospital readmissions are associated with increased harm to patients, increased medical costs, and negative hospital reputation. With the identification of at-risk patients, a crucial step toward improving care, appropriate interventions can be adopted to prevent readmission. This study aimed to build machine learning models to predict 14-day unplanned readmissions. Methods We conducted a retrospective cohort study on 37,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In order to address the study objectives, we used standard evaluation indices to evaluate our ML models, as suggested by previous research, [25] including the accuracy, precision score (positive predict rate), recall score (sensitivity), AUC (area under the receiver operating characteristic curve), F1 score (the harmonic mean of precision and recall scores), and the precision-recall curve for the training dataset. We used the calibration J o u r n a l P r e -p r o o f plot (i.e., a plot showing whether the risk prediction of BCRL was accurate) to examine the performance of the validation dataset.…”
Section: Discussionmentioning
confidence: 99%
“…In order to address the study objectives, we used standard evaluation indices to evaluate our ML models, as suggested by previous research, [25] including the accuracy, precision score (positive predict rate), recall score (sensitivity), AUC (area under the receiver operating characteristic curve), F1 score (the harmonic mean of precision and recall scores), and the precision-recall curve for the training dataset. We used the calibration J o u r n a l P r e -p r o o f plot (i.e., a plot showing whether the risk prediction of BCRL was accurate) to examine the performance of the validation dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao QY et al developed a model for predicting extubation failure in intensive care units with 11 ML algorithms and the CatBoost algorithm showed the best performance in the internal and prospective validation set ( 37 ). Lo YT et al built a risk stratification tool for predicting 14-day unplanned readmission, in which the CatBoost algorithm showed the best performance in the 5-fold cross-validation (AUROC:0.9903) of four selected ML algorithms ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the following errors were reported: Jah Chiehen Liao’s name was misspelled as ‘Jay Chie-hen Liao’ A note marking Yu-Tai Lo and Jay Chiehen Liao as co-first authors was missing A grant number was missing in the Acknowledgement declaration …”
Section: Correction To: Bmc Med Inform Decis Mak (2021) 21:288 101186...mentioning
confidence: 99%